Factors and interventions determining the functioning of health care teams in county-level hospitals in less affluent areas of China: a qualitative study - Hujie Wang; Jeroen van Wijngaarden; Martina Buljac-Samardzic; Joris van de Klundert; Joris van de Klundert (Frontiers Media S.A., 2023)
BackgroundTeamwork is essential for the quality and safety of care, and research on teamwork in health care has developed rapidly in many countries. However, evidence from less affluent, non-Western countries is scarce, while improving teamwork may be especially relevant to be able to increase the quality of care in these settings. This study aims to understand the main factors that influence, and interventions used to improve, the functioning of health care teams in the context of county-level hospitals in less affluent areas of China.MethodsWe conducted semistructured interviews to explore the factors that influence team functioning and the interventions implemented to improve team functioning in these hospitals. 15 hospital presidents and 15 team leaders were selected as respondents.ResultsFrom the interviews, we have identified five main factors that influence team functioning in these hospitals: "stuck in the middle", local county setting, difficulty in attracting and retaining talent, strong focus on task design, and strong focus on leadership. The interventions for improving team functioning can mostly be categorized as the following: 1) measures to attract and retain talent (e.g., increase salary, train talent in national or provincial level hospitals, and provide fast-track promotions), 2) interventions focused on monodisciplinary teams (e.g., changing the team structure and leadership, and skill training), and 3) interventions to establish and improve multidisciplinary teams (e.g., simulation training and continuous team process improvements).ConclusionWith the introduction of multidisciplinary teams, interventions into team processes have started to receive more attention. The findings depict an overview of the main factors and interventions as specifically relevant for team functioning in county-level hospitals in less affluent areas of China and may help these hospitals benefit from additional process interventions to improve teamwork and the quality of care.